Thromboembolic event in a patient of immune thrombocytopenic purpura: a case report - Nazar, Maimoona; Nasir Ashraf; Laiba Sultan; Laiba Sultan (Journal of the Pakistan Medical Association, 2025)
Immune Thrombocytopenia Purpura (ITP) is an autoimmune disorder characterised by a low blood platelet count, which is attributed to both decreased megakaryocyte production in the bone marrow and the generation of autoantibodies causing platelet destruction in the spleen. Individuals with autoimmune conditions are highly susceptible to pulmonary embolism. This case involves a 39-year-old female with ITP who developed thromboembolisms. A comprehensive investigation into prothrombotic risk factors, including obesity, smoking, family history of thromboembolism, and ITP-related interventions such as prolonged corticosteroid use or splenectomy, revealed insignificant results, except for the patient's history of receiving corticosteroid therapy. Despite the disparate pathogenesis of thromboembolism (TE) and ITP, recent events of TE in ITP patients have been observed. This report underscores the potential life-threatening complications in ITP and aims to explore their causes and pathogenesis for ensuring optimised patient care. Key Words: Immune thrombocytopenia, autoantibodies, autoimmune, thromboembolism, corticosteroid therapy, splenectomy.